Hepatitis E Virus Seroprevalence and Associated Risk Factors in Pregnant Women Attending Antenatal Consultations in Senegal - Abou Abdallah Malick Diouara; Seynabou Lo; Cheikh Momar Nguer; Assane Senghor; Halimatou Diop Ndiaye; Noël Magloire Manga; Fodé Danfakha; Sidy Diallo; Marie Edouard Faye Dieme; Ousmane Thiam; Babacar Biaye; Ndèye Marie Pascaline Manga; et al. (Viruses, 2022)
In West Africa, research on the hepatitis E virus (HEV) is barely covered, despite the recorded outbreaks. The low level of access to safe water and adequate sanitation is still one of the main factors of HEV spread in developing countries. HEV infection induces acute or sub-clinical liver diseases with a mortality rate ranging from 0.5 to 4%. The mortality rate is more alarming (15 to 25%) among pregnant women, especially in the last trimester of pregnancy. Herein, we conducted a multicentric socio-demographic and seroepidemiological survey of HEV in Senegal among pregnant women. A consecutive and non-redundant recruitment of participants was carried out over the period of 5 months, from March to July 2021. A total of 1227 consenting participants attending antenatal clinics responded to a standard questionnaire. Plasma samples were collected and tested for anti-HEV IgM and IgG by using the WANTAI HEV-IgM and IgG ELISA assay. The overall HEV seroprevalence was 7.8% (n = 96), with 0.5% (n = 6) and 7.4% (n = 91) for HEV IgM and HEV IgG, respectively. One of the participant samples was IgM/IgG-positive, while four were declared indeterminate to anti-HEV IgM as per the manufacturer’s instructions. From one locality to another, the seroprevalence of HEV antibodies varied from 0 to 1% for HEV IgM and from 1.5 to 10.5% for HEV IgG. The data also showed that seroprevalence varied significantly by marital status (p < 0.0001), by the regularity of income (p = 0.0043), and by access to sanitation services (p = 0.0006). These data could serve as a basis to setup national prevention strategies focused on socio-cultural, environmental, and behavioral aspects for a better management of HEV infection in Senegal.